FEATURES OF THE DEGREE OF MINERALISATION IN THE PERIODONTAL BONE TISSUE OF RAT PERIODONTAL BONE TISSUE UNDER CONDITIONS OF PEROXIDATION-INDUCED PERIODONTITIS, DIETARY PROTEIN DEFICIENCY, AND THERAPEUTIC-PREVENTIVE MEASURES - Hurtova, Y.M.; Shnaider, S.A.; Dienha, O.V.; Godovanets, O.I.; Baleha, M.I.; Demianchuk, Yu.V.; Khodorchuk, K.V. (World of Medicine and Biology, 2025)
The study was devoted to the researching of the effect of the therapeutic and prophylactic complex on the degree of mineralisation of periodontal bone tissue in rats with peroxidative periodontitis and protein deficiency. The experiment involved 30 male Wistar rats divided into three groups: intact, a group with combined pathology and a group with combined pathology, which received the therapeutic and prophylactic complex. Protein content and calcium level were determined in periodontal bone homogenates, and the degree of mineralisation was calculated from the ratio of calcium to protein content. A marked reduction in bone destruction accompanied by stabilisation of lysosomal membranes and improved mineralisation in rats treated with the complex highlights the potential application of this therapeutic strategy in clinical settings. By eliminating oxidative stress and nutrient deficiencies, the complex may play a key role in preventing osteopenic changes and improving periodontal tissue health in patients at high risk of combined pathologies.
Keywords: periodontitis; bone tissue; rats; experiment; biochemical markers